Effect of Different Root Canal Prepration Methods on Roots Fracture Resistance of Endodontically Treated teeth (In Vitro study) (Journal of Hama University, 2020)
Aims and Objectives:The aim of this laboratory study was to evaluate root fracture of endodontically treated teeth after canals preparations using two different systems: Reciprocblue (R25), and Mtwo(06/25)Materials and Methods: thirty extracted mandibular premolars were selected with completed, straight and single canal root and free of caries , resorption or previous treatment. The teeth crowns were removed and root length was adjusted to 16mm. Teeth were devided into 3 groups of 10 teeth each. Group I (control group) is non instrumented teeth. Group II: canals were prepared using Mtwo rotary files.Group III: canals were prepared using Reciprocblue file .The root were vertically loaded using testing machine (TESTOMETRIC ,USA) and the load causing fracture was detected and recorded in newton. ANOVA test was used to show the nature of difference of the fracture load of studied groups, ,LSD test for dual comparison between groups was used. All stastical analysis was performed at 95% level of confidence. The results showed stastically significant differences regarding fracture load between control group and other  groups, also showed stastically significant differences between Reciprocblue and Mtwo groups, conclusion: Reciprocation motion reduce the root fracture resistance compared with  continuous rotation motion